PEMAHAMAN GURU TENTANG PEMBELAJARAN MENDALAM DI SMP NEGERI 5 SATU ATAP TOLONUO - Irfandi R Hi. Mustafa; Fahrun Yamin; Iswadi M Ahmad; Fitri Ayu Lestari; Sirman Jabir; Hafisari Ismail (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
This study aims to describe the implementation of the concept of deep learning at SMP Negeri 5 Satu Atap Tolonuo based on the perceptions and direct experiences of teachers. The method used was qualitative interviews with six teachers from various subjects. The results of the study show that teachers have understood the essence of deep learning as student-centered learning, emphasizing conceptual understanding, critical thinking, and application in real-life contexts. The implementation was carried out through the design of contextual lesson plans, the use of discussion and problem-based learning methods, and authentic assessments such as projects and portfolios. The main obstacles encountered include limited facilities, diversity in student abilities, and time constraints. The main supporting factors are the support of the principal and collaboration among colleagues. Positive changes were observed in students, such as increased activity, courage to express opinions, and collaboration skills. For optimization, it is necessary to improve teacher training and add supporting facilities.